Waist Circumference, Weight, and Body Mass Index of Iranians Based on National Non-Communicable Disease Risk Factors Surveillance - B Larijani; HR Aghaei Meybodi; MH Forouzanfar; H Kashani; SH Abbaszadeh Ahranjani; M Aalaa; MR Mohajeri-Tehrani (Tehran University of Medical Sciences, 2012)
Background: Obesity is an important and life-threatening disease, associated with different chronic conditions such as cardiovascular disease, diabetes, and dyslipidemia. We sought to address the paucity of information on the trends of anthropometric indices such as weight, waist circumference, and body mass index in the adult population of Iran. Methods: We drew upon data from the First Non-communicable Disease Survey in Iran in 2005. In total, 79,611 participants between 20 and 64 years old were selected via the random multistage cluster sampling. The Lambda Median Scale method was applied to construct normal curves for anthropometric indices.Results: The mean of waist circumference in both genders increased with age and in all the age groups except those between 20 and 24 years old was higher in the women. The mean of body mass index was higher in all the age brackets in the women, but the means of weight and height were higher in the men. The association of theses indices with diabetes, hypertension, and dyslipidemia was stronger in men. Conclusion: The ranges of waist circumference and body mass index in Iranian population are different from those of other countries. The higher body mass index and waist circumference in females and the direct association between obesity and chronic diseases, is advisable that the effects of this phenomenon be fully investigated and due heed be paid to the importance of lifestyle modification.